Pragmatisme Pendidikan Kewargaan Digital Dalam Kepungan Algoritma Suatu Refleksi Aksiologi - Feriyansyah Feriyansyah; Septiana Dwiputri Maharani (Jurnal Civic Hukum, 2023)
This article aims to examine values in the study of pragmatic digital citizenship education and the crisis of values amidst algorithmic domination. The challenge of digital citizenship education in the midst of algorithmic domination reflects a crisis of values in the process of digital citizenship education with an axiological reflection approach. This article provides an answer through an axiological reflection approach to pragmatic digital citizenship education based on practical experiences in algorithmic domination to obtain practical significance in digital citizenship education. The pragmatism of values is closely related to individual experiences and transactions in the digital social space as an environment in which individuals live and act. Digital citizenship experiences shape the role of individuals by bringing value systems as a basis for decision-making in the digital realm. Digital citizenship experiences shape human roles as subjects in the digital social space. Pragmatic digital citizenship education is a technology to engineer individual experiences as digital citizens to become subjects who have value systems as a basis for activities and gain benefits in the digital social space as an ultimate goal.